"Ornithological eutrophication" as a source of allochthonous nutrient enrichment in Anavilundawa reservoir, Sri Lanka. Issue 5 (10th November 2015) - Gunaratne, Anushka M.; Jayakody, Sevvandi; Amarasinghe, Upali S.
Abstract : Mass aggregation of waterfowls for breeding, results in allochthonous nutrient inputs into aquatic systems. This study evaluated accumulation of bird droppings as allochthonus nutrient input and its fluctuations in Anavilundawa International Ramsar Sanctuary in Sri Lanka where Asian openbill ( Anastomus oscitans ) mass breeding occurs annually. Reservoir was divided into four strata: Inlet, breeding ground, reservoir centre and outlet. The highest nutrients levels (NO3 −, PO4 3−, NH4 +, alkalinity) and the lowest dissolved oxygen and pH levels were recorded in breeding grounds for both surface and bottom water. The highest turbidity was recorded in inlet surface and centre bottom water. Canonical Variate Analysis of water quality parameters indicated the significantly distinct influence of ornithological eutrophication on surface water of four strata whilst, showing similarities in water quality of bottom layers in inlet and outlet. In the breeding ground, surface water was covered with thick mats of aquatic flora consisting of Water hyacinth, Salvinia, duckweed and Polygonum. Therefore, it is concluded that in addition to dilution, amelioration of water quality could also be happening due to absorption by plants. Due to interactions between invasive plants and waterfowls, restoration with native aquatic flora is needed to be considered to regain reservoir resilience and self‐sustenance.